Pre-Anesthesia Assessment and Preparation - Imai Indra; Kulsum Kulsum (Budapest International Research and Critics University, 2020)
The aims of the study is to find out pre – anesthesia assessment and preparation. The result of the study shows that Pre-anesthesia is an important first step in a series of anesthesia procedures performed on patients who are planned to undergo surgery. The things that need to be done include history taking, physical examination, laboratory examination, and physical status classification. Preparations are made at the clinic or at home for outpatients, in the treatment room, in the Central Surgery Installation (IBS) room, and in the operating room. Pre-anesthesia physical status assessment is very important. Anesthesia is not differentiated based on the size of the surgery but consideration of the choice of anesthesia techniques that will be given to patients is very complex and comprehensive considering all types of anesthesia have risk factors for complications that can threaten the patient's life